Está en la página 1de 9

F(T, V, N 1 , ··· , N r ) =

r

i=1

F(T, V, N i )

U = r i=1 U i S = i=1 r S i U, S U i , S i V V i = V T i = T

F

=

U TS

r r

=

i=1

r

=

i=1

r

=

i=1

U i T

i=1

S

i

U i TS i

F(T, V, N i )

V 1 V 2

N

F

F = U ST =f = usT =df = duT dssdT = duT ds = f = uT s

T

 u = cRT − a v

= u = a

1

v

2

1

1

v

s =

Rln [(v b)(u + a/v) c ] + s 0

s

=

=

=

b u 2 Rln v v 2 1 b

u

1

+ a/v

a/v c

c

+

Rln v 2 b

v

1

b cRT 2 cRT 1

Rln v 2

b

b

v

1

f

= F

=

=

=

u T s

a

1

v

1

1 2 RTln v 2 b

v

b

v

1

aN 2

1

V 1

V 2 NRTln V 2 bN

1

bN

V

1

G

 G = U − ST + V P =⇒ g = u − sT + vP =⇒ dg = du − T ds + vdP + P dv =⇒ g = u − T s + 1→2 vdP + P dv

 P = =⇒ dP = =⇒ vdP = P dv = =⇒ vdP + P dv = =

RT

v b a

v

RT b) 2

RT v b) 2

RT v b a

v

a 2 dv

v

dv

(v

+

+ a

v

(v

dv

(v b) 2 + v + v b a

v

RT v

a

RT

RT

1

v b

(v b) 2 dv

v

dv

12 vdP + P dv

=

=

=

=

=

=

RT

v

v

1

2

1

v b

(v b) 2 dv

v

RT ln v 2 b

v

1

b

v

v 2

v

b) 2 dv

1 (v

t = v b

RT ln v 2 b

v

1

b

v 2 b

v 1 b

RT ln v 2 b

v

1

b

v 2 b

v 1 b

(t + b)

t

1

t

2

dt

b 2 dt

t

RT ln

v 2 b v 1 b

ln v v 2 1 b

b b

1

v

2

b

1 b

v

1

bRT

1

v

2

b

1 b

v

1

g

= G

=

=

=

u T s + 12 vdP + P dv

a 1

v 1

aN 2

2 RTln v 2 b

1

v

v

1

b bRT

1

1

b

1

V 1

b

v 1

v 2

bN bN 2 RT

V 2 NRTln V 2 bN

1

V

1

1

V 2 bN

V 1 bN

1

Ω = aV T 5/2 e

µ

RT

N = N (T, V, µ) P = P (T, V, N )

F = F (T, V, N )

G = G(T, P, N )

S = S(N, T, V ) S = S(T, P, N )

H = H(S, P, N )

 ∂Ω ∂µ − aV T 5/2 µ e RT RT − aV T 3/2 µ e RT RT µ e RT
 −N = = =

=N = aV RT T 3/2

 −P = = =⇒ P = = =

∂V

aT 5/2 e

T aT 3/2 e

RN

T

µ

RT

µ RT

V

RNT

V

F

= U T S

Ω = U T S µN =F = Ω + µN

N

= aV T 3/2 RT

e

RT =µ = RTln aV RN T 3/2

µ

Ω = aV T 5/2 e RT = aV T 5/2 · aV RN T 3/2 = RNT

µ

F

= Ω + µN

= RNT RNTln aV RN T 3/2

= RNT 1 + ln aV RN T 3/2

G

= U T S + P V

= U T S + P V µN + µN = µN

 P = µ =⇒ = RT =⇒ µ =

aT 5/2 e

ln

µ

RT

5/2

P

aT

RTln

5/2

P

aT

G = µN = RNTln

5/2

P

aT

 −S = = = = = =⇒ S =

∂T

5 aV T 3/2 e RT + aV T 5/2 ·

µ

2

5 NR + aV T 1/2

2

R

· µe

µ

RT

µ

RT 2 · e

µ

RT

5 NR + aV T 1/2

2

R

RN

3/2 · RTln

· aV T

2 5 NR NRln aV RN T 3/2

RN

5

2

+

ln aV T 3/2 RN

RN

3/2

aV T

S = S(T, P, N ) P V = NRT

H = U +P V

S

= RN 5

2 + ln aV T 3/2

RN

=

RN

5

2

+

ln aV T 5/2 RNT

=

RN 2

5 + ln aT 5/2

P

S =

=ln aT 5/2 =

P

 =⇒ T 5/2 = =⇒ T =

RN 2 5 + ln aT 5/2

P

S

NR 5 2

P a · e

P

S

5

a

NR 2

2/5

· e

2S

5NR 1

F = U T S =H = F +T S+P V = F +T S+NRT = F +(S+NR)T

F

= RNT 1 + ln aV T 3/2

RN

= RNT 1 + ln aV T 5/2

RNT

= RNT 1 + ln aT 5/2

P

=

RN P

a

2/5

· e 5NR 1 · 1 +

2S

S

NR 2 5

2/5
=

RN P

a

· e

5NR 1 · 3

2S

2 NR

S

H

= F + (S + NR)T

=

RN P

a

2/5

· e

5NR 1 · 3 2

2S

NR + (S + NR) P

S

a

=

P

a

2/5

e 5NR 1 · S + NR + NR 3 2

2S

2/5
=

5

2 NR P

a

e

2S

5NR 1

NR

S

2/5

· e

2S

5NR 1

0 C 10l 1l 6l 5l

dW = dF = dF 1 dF 2

dF i

=

=

=

S i dT i P i dV i + µ i dN i

P i dV i

N i RT i

dT i = dN i = 0

dV

i

V

i

=

RT dV i

V

i

=⇒ − F = RTln V i,f

V i,0

dT i = 0 T i = T dN i = 0

W

= F 1 F 2

= RTln V 1,f + RTln V 2,f

V 2,0

V

1,0

= RT ln 5 + ln

= RTln(3)

= 2,5kJ

1

10

6

F T R